HUKUM KEPERAWATAN: MENDEFINISIKAN DAN MELINDUNGI TUGAS, TANGGUNG JAWAB, DAN HAK HUKUM PERAWAT DALAM SISTEM PELAYANAN KESEHATAN - Hotmaria Hertawaty Sijabat (JOURNAL OF LAW AND NATION, 2026)
This study analyses nursing law in Indonesia based on Law No. 38 of 2014 on Nursing to define the duties, responsibilities, and legal rights of nurses in the health care system. Through a normative juridical approach with a literature review of primary and secondary legal materials, the study identified two main discussions: (1) the definition and scope of nurses' duties, which include nursing care, delegation of authority, and civil, criminal, and administrative responsibilities; and (2) preventive and repressive legal protection mechanisms through standard operating procedures (SOPs), professional organisations, and legal assistance. The results show that although the legal framework is comprehensive, implementation remains weak due to unclear delegation of authority and low legal literacy. Recommendations include strengthening derivative regulations, legal training, and non-punitive investigation systems to enhance the professionalism and protection of nurses.